PENGARUH FAKTOR PSIKOLOGI PADA INVESTOR MUSLIM DI PASAR MODAL - Nini Sumarni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The focus of this study is to determine the psychological factors that influence the behavior of Muslim investors in the capital market. Besides, it is to find out the psychological factors of Muslim investors can be used to predict the type of investment (stocks, mutual funds, bonds) chosen by Muslim investors. This research is exploratory. This study tries to provide an overview of the influence of psychological factors on investment choices and the behavior of Muslim investors in the capital market. To prove the hypothesis that has been made, a linear regression analysis technique is used which is carried out on the results of the questionnaire that has been filled by the respondents. Linear regression analysis using SPSS version 16.0. The independent variables tested were psychological factors which included; Overconfidence; Data Mining; Status Quo; Social Interaction; Emotion; Mental Accounting; Representativeness; Familiarity; Considering The Past; Fear and Greed; Self Control; and Loss Aversion. The dependent variable tested is Muslim investor behavior which includes; risk seeker (likes risk) and risk averter (fear of risk). Overall, R values of 0.653 and R square (R2) of 0.426 were obtained. the coefficient of determination of 13.78% states that the type of investment influenced by psychological factors is only 13.78% and the capital is 86.22% influenced by other factors.